Development of Inflip-Based Footwork Exercise Movement for Extracurricular Badminton Students at Taman Siswa Middle School Turen - Prastya, Ricky Ican Agil; Irmawati, Farizha (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
By combining the footwork training model into a flip book as an application or software in training, this study also aims to provide a training model product with new, more interesting innovations. Which will later make it easier for coaches to compile the stages of basic techniques that will be given to students, with the hope that the training process can run smoothly and effectively. This study is the development of a footwork movement training model for badminton extracurricular students using flipbook media. The development of this product consists of 5 stages, namely Analysis, Design, Develop, Implement, and Evaluate, which are modified to suit this study. This development research produces a footwork movement training model using flipbook media that is feasible and validated by media experts and badminton experts and is able to improve the understanding of badminton concepts in extracurricular students of SMP Taman Siswa Turen.